Pengaruh Intensitas Bullying Terhadap Pola Komunikasi Interpersonal Pada Mahasiswa FISIP UNDIP Program Studi Ilmu Komunikasi Angkatan 2017 - Sekarningtyas, Prilia; ., Sunarto (Interaksi Online, 2019)
Many people these days got violence within themselves or can be said to be exposed to bullying. Such behavior occurs a lot through verbal and non-verbal. That behavior happens a lot among teenagers. The factor is to conduct social interactions in various environments they occupy, such as schools, campus, social environments, and many more. Communication is one of the factors where the occurence of bullying behavior among teenagers, because by conducting a good communication process that is effective or ideal, the behavior will not occur. The purpose of this research is to explain the intensity of bullying influence on interpersonal communication patterns in students. This research use Social Learning Theory. The population in this research are students class of 2017 in communication science. Data analysis was performed using quantitative analysts with Simple Linear Regression Correlations. In this research said that social and family environmental factors are the most important factors in influencing a person's character, where they will follow or imitate other people's behavior by looking at the person's treatment. By looking, other people will do this to their peers. Where when someone commits acts of violence or bullying, it can make an impact on the behavior of others. One of the impacts that will occur is their interpersonal communication pattern. The pattern of interpersonal communication itself has two kinds, namely ideal communication and communication are not ideal. When there is a factor, their communication pattern will change to not ideal, or it can be said to be bad. So, with the influence of the intensity of bullying will have a negative impact on one's interpersonal communication patterns to be not ideal or bad. The results of this research indicate that there is a hypothesis that there is an influence of Bullying Intensity on Interpersonal Communication Patterns on UNDIP FISIP students in 2017 communication study program.